Good Digital Records Don’t Just “Happen”: Embedding Digital Recordkeeping as an Organic Component of Business Processes and Systems - Cunningham, Adrian (Archivaria, 2011)
This article considers why, after so many years of addressing the challenge of electronic recordkeeping, so few organizations are doing a good job of making and keeping the born-digital essential evidence of their decisions and activities. Using the experience of the National Archives of Australia as an example, it critiques approaches to digital recordkeeping implementation that focus too rigidly on process over outcomes, and on the tendency of organizations to deploy records systems that are disconnected from business systems and business processes. The second half of the article describes the results of an International Council on Archives (ICA) project that focused on addressing these challenges by developing a suite of three interrelated statements of globally harmonized principles and functional requirements for digital records systems in office environments. In particular, the article highlights the third module of the ICA suite, which addresses the core requirements for making and keeping records in business systems. RÉSUMÉ Ce texte examine pourquoi, après plusieurs années consacrées à affronter le défi de la gestion de l’information électronique, si peu d’organisations réussissent à créer et à sauvegarder les preuves essentielles numériques de leurs décisions et de leurs activités. En se servant de l’expérience des Archives nationales de l’Australie à titre d’exemple, il critique les approches d’implantation d’une gestion de l’information numérique qui mettent l’accent de façon trop rigide sur le processus au détriment des résultats et il critique aussi la tendance des organisations de se servir de systèmes de gestion de documents qui n’ont aucun lien avec les systèmes et les processus opérationnels. La deuxième moitié de ce texte décrit les résultats d’un projet du Conseil international des archives (CIA) qui visait à relever ces défis en développant une suite de trois énoncés de principes et d’exigences fonctionnelles intereliés et harmonisés pour les systèmes de gestion de documents numériques dans l’environnement de travail. En particulier, ce texte met en évidence le troisième module de la suite du CIA qui aborde les exigences de base pour créer et conserver des documents dans les systèmes administratifs